Exploring the impact of wait times and service delays on patient engagement and trust in healthcare facilities - Al-Kaabi, Fatima (International research journal of management, IT and social sciences, 2025)
Prolonged wait times and service delays continue to be central issues in the UK’s NHS, with far-reaching consequences for patient engagement and trust. How these operational problems affect patient attitudes is critical to the development of patient-centred care initiatives. This research aimed to investigate the impact of wait times, service delays, and associated communication variables on patient engagement and Trust in NHS healthcare settings. A quantitative cross-sectional survey was conducted among 500 adult NHS users who had utilized healthcare services within the last 12 months and experienced delays due to waiting times. Data were gathered using a standardised questionnaire that included demographics, experiences of wait times, communication, engagement, and trust. Hierarchical multiple regression analysis was conducted using SPSS, building models progressively on service experience and facility perception variables to determine predictive capability. The baseline model, which included only demographics, predicted negligible variance in engagement (R² = 0.034). Adding variables related to service experience improved model performance substantially (R² = 0.446). Wait time (β = -0.1987, p < 0.001), delay experience (β = -0.22, p < 0.001), and ease of booking (β = 0.1103, p < 0.001) were all significant predictors. Information about delays also had a positive impact on engagement.